Role of development policies in combating climate change issues in Indian agriculture: A first order assessment of irrigation and fertilizer policies - Joshi, Pramod Kumar; Aggarwal, Pramod K.; Tyagi, N.K.; Pandey, Divya (International Association of Agricultural Economists, 2015)
The Government of India has pursued policies supporting intensive use of irrigation and fertilizer for the development of agrarian economy. A first order assessment of the impacts of these development policies on mitigation, adaptation, resilience and sustainability has been made quantitatively with the help of specific performance indicators. The analysis is based on the hypothesis that productivity enhancement serves better to deal with climate change as it minimizes deforestation and therefore reduces intensification of greenhouse gas emissions. The assessment establishes that development policies have been highly successful in reducing potential greenhouse gas intensification and increasing the adaptation capacity in terms of food grain production. The performance of policies, particularly of water resources development, with respect to sustainability is, however, questionable. The relatively new initiative on micro irrigation fares well in respect of most performance indicators, calling for further policy support for its scaling out. Joshi, Pramod K.; Aggarwal, P.K.; Tyagi, N.K.; Pandey, Divya